Social Support in Disaster Evacuations: A Systematic Review for Information Systems Research - Grace, Rob; Ginjupalli, Vinayana; Chauhan, Apoorva (Proceedings of the International ISCRAM Conference, 2026)
Disaster evacuations displace thousands each year, with households relying on family and friends to make decisions, secure shelter, and recover before returning home. Yet research on social support remains fragmented, typically focusing either on health outcomes or on evacuation logistics such as transportation and sheltering behavior. We address this gap by reviewing 31 empirical studies published between 2005 and 2024 and synthesizing an integrated framework that captures structural, perceived, and received dimensions of social support, along with emotional, informational, and instrumental types. We further link social support to both psychological and behavioral evacuation outcomes, highlighting its central role in communities’ capacity to prepare for, carry out, and recover from evacuations. This framework advances information systems research by informing evacuation simulation and decision-support systems that anticipate social-support-driven behaviors and health impacts, identify populations with unequal access to informal support, and design tools to connect socially isolated evacuees to formal resources.